The role of birth order in infant mortality in Ifkara DSS area in rural Tanzania - Sangber-Dery, Matthew Dery (My University, 2010)
Introduction: Studies of factors affecting infant mortality have rarely considered the role of birth order. Despite the recent gains in child mortality in Tanzania, infant mortality rate is still high (68 per 1000 live births) according to the Tanzania Demographic Health Survey (2004-5). This study investigated the risk factors associated with infant mortality in Ifakara Health and Demographic Surveillance Systems area in rural Tanzania from January 2005 to December 2007 with specific reference to birth order, and identified causes of infant death for the study period. Materials and Methods: The study was a secondary analysis of existing data from the Ifakara Health and Demographic Surveillance Systems (HDSS). Child data for 8916 live births born from 1st January 2005 to 31st December 2007 were extracted for analysis. The binary outcome variable was infant mortality. Tables and graphs were used to describe the distribution of maternal demographic and study population characteristics. Poisson regression analyses were used to establish the association between infant mortality and exposure variables. Results: We recorded 562 infant deaths. Neonatal mortality rate was 38 per 1000 person-years while infant mortality rate was 70 per 1000 person-years. Birth order of 2nd to 5th was associated significantly with 22% reduced risk of infant mortality (IRR=0.78, 95%CI: 0.64, 0.96; p=0.02) compared with first births. The infant mortality rates per 1000 person-years for first births was 84, 2nd to 5th was 66 and sixth and higher was 71 per 1000 person-years. Male infants were 17% more at risk of infant deaths as compared to their female counterparts, but not statistically significant (IRR=1.17, 95%CI: 0.99, 1.38; p=0.06). Mothers aged 20 to 34 years had 19% reduced risk of infant death (IRR=0.81, 95%CI: 0.65, 1.00; p=0.05) as compared v to mother of less than 20 years of age. Singleton births had 71% reduced risk of infant mortality (IRR=0.29, 95%CI: 0.22, 0.37; p<0.001) compared with twin births. Mothers who did not attend antenatal care had 2% reduced risk of infant deaths (IRR=0.98, 95%CI: 0.49, 1.97) but not statistically significant compared with mothers who attended antenatal care. Mothers who delivered at home were 1.05 times more at risk of infant deaths but not statistically significant (IRR=1.05, 95%CI: 0.89, 1.24; p=0.56). Mothers who had no formal education were 1.41 times more likely to have infant deaths (IRR=1.41, 95%CI: 0.72, 2.79; p=0.32) as compared to those who had education beyond primary. When adjusted for sex, maternal age and twin births, second to fifth birth order had 20% reduced risk of infant death (IRR=0.80, 95%CI: 0.61, 1.03; p=0.08), but statistically not significant as compared to first births. Malaria (30%), Birth injury/asphyxia (16%), Pneumonia (10%), Premature and/or low birth weight (8%), Anaemia (3%) and Diarrhoeal diseases (2%) were the major causes of infant deaths from 2005 to 2007. Discussion and conclusion: First births and higher birth orders were associated with higher infant mortality. Twin birth was a risk factor for infant mortality. The health systems should be strengthened in providing care for mothers and child survival. We recommend that the high-risk group, first or sixth or higher pregnancies, need special care and the existing health management system may be strengthened to create awareness among potential mothers for seeking appropriate health care from the beginning of pregnancy. Also, antenatal care follow-up can be emphasized for high-risk mothers. Efforts to control mosquitoes must be accelerated in the Ifakara sub-district.
MSc (Med) (Population-Based Field Epidemiology), Faculty of Health Sciences, University of the Witwatersrand
Keywords: birth order; infant mortality; developing countries; Tanzania